2014
DOI: 10.1021/ef4024788
|View full text |Cite
|
Sign up to set email alerts
|

Probing Maltene–Asphaltene Interaction in Crude Oil by Means of NMR Relaxation

Abstract: The distribution of NMR relaxation times and diffusion coefficients has been employed for modeling the composition of typical crude oils both in bulk and in the reservoir rock. Although the relation of relaxation times and diffusion coefficients with viscosity and molecular size in a typical maltene composition has been established for bulk oils, it is known that the presence of asphaltene affects the relaxation times in a complex way not sufficiently understood so far. In particular, it is expected that the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 32 publications
5
30
0
Order By: Relevance
“…For all substances, the 19 F relaxation times ratios T 1 /T 2 were measured to be between 1.17 and 1.25, close to the expected value of 1.0 for fast tumbling molecules in a low-viscosity liquid [23]. Fig.…”
Section: Resultssupporting
confidence: 78%
“…For all substances, the 19 F relaxation times ratios T 1 /T 2 were measured to be between 1.17 and 1.25, close to the expected value of 1.0 for fast tumbling molecules in a low-viscosity liquid [23]. Fig.…”
Section: Resultssupporting
confidence: 78%
“…Given that the surface diffusion of the hydrocarbons close to the asphaltene nano-aggregates is 5.3 times smaller than the bulk diffusion, as shown by 2D NMR DOSY experiments [110], and given a molecular size d oil = 0.655 nm for the oil (octane), this latter time s S gives an average radius of exploration for 2D hydrocarbon diffusion, r 2D ¼ The very long residence time found (s S ) s m ) proves there is efficient interaction between maltene and asphaltene, and agrees with the theoretical model of anisotropic 2D diffusion of hydrocarbons in proximity to the asphaltene nano-aggregates having very slow rotation on such a time scale [136]. A complementary study of fluorine-containing tracer molecules in natural oils of different asphaltene content was proposed by Stapf et al for proving the selective maltene-asphaltene interaction by analysing frequencydependent relaxation results [139]. For the crude oil largely without asphaltene (i.e.…”
Section: Structure and Dynamics Of Crude Oils In Bulksupporting
confidence: 78%
“…In quantitative studies, the EPR signal is found to correlate with the asphaltene content. The NMR relaxation properties of liquid components in oil, the so-called maltenes, were likewise found to correlate with the asphaltene content [43,44], suggesting that the latter contain the largest amount of unpaired electrons in crude oil, and therefore act as a relaxation agent in analogy to contrast agents in aqueous solution. Current literature concludes that free, delocalized electrons and vanadyl ions (VO 2+ ) constitute the major contributions to the EPR spectrum, though their relative proportion varies greatly.…”
Section: Introductionmentioning
confidence: 96%